On the Conception of Motion (From the History of Lithuanian Materialism) - Barzdaltis, Juozas (Problemos, 1972)
An analysis of the conception of motion as presented by Lithuanian materialists towards the end of the 19th and at the beginning of the 20th centuries is given in the article. When solving the problem of matter, Lithuanian materialists and atheists of that time associated it with the problem of motion. They considered matter to be not inanimate and passive but active and constantly changing. Motion, they emphasized, should be taken as a basic, essential and eternal property of matter. Rejecting the hypothesis of the mysterious external “first push” as a source of motion, thus approaching dialectical understanding of the given phenomenon, they did not succeed, however, in explaining the true source and real cause of motion.